Culture, space and the nation-state from sentiment to structure - Gupta, Dipankar (New Delhi Sage, 2000)
This book extend the concerns of anthropology beyond the study of village life and caste observances to include considerations of the nation state. The book is divided in to two parts,the first part is based on the nation states are bound by strong sentim
Keywords: State; Culture; Social Institution; Political geography